2013
DOI: 10.1179/1476830512y.0000000013
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin A, vitamin E and apolipoprotein E status with mild cognitive impairment among elderly people in low-cost residential areas

Abstract: The study highlighted the importance of maintaining good nutritional status and vitamin A status for optimal cognitive function. The presence of APOEε4 allele has a prominent role in affecting vitamin E levels, particularly among cognitively healthy elderly in our unique population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…We did not observe the effect of APOE rs429358 or rs7412 polymorphism on cognition (MoCA score) in the old Chinese subjects. This result was in line with Shahar and coworker’s study [ 35 ]. In their study, the authors found that APOE genotype was not associated with mild cognitive impairment (MCI).…”
Section: Discussionsupporting
confidence: 93%
“…We did not observe the effect of APOE rs429358 or rs7412 polymorphism on cognition (MoCA score) in the old Chinese subjects. This result was in line with Shahar and coworker’s study [ 35 ]. In their study, the authors found that APOE genotype was not associated with mild cognitive impairment (MCI).…”
Section: Discussionsupporting
confidence: 93%
“…Alzheimer’s disease (AD) is the commonest type of dementia and it is postulated to cause 60– 80% of cases worldwide (WHO, 2020; Alzheimer’s Association [AA], 2020). While older age group is recognized as the greatest risk factor for AD (AA, 2020; Rivan et al, 2020; Ibrahim et al, 2019), there are multiple other factors that are responsible for cognitive decline (Hussin et al, 2019; Lee et al, 2012; Shahar et al, 2013; Meramat et al, 2015). One of the most important non-modifiable risk factors is the apolipoprotein E (APOE) genotype which has been implicated in late-onset Alzheimer’s disease (LOAD).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, vitamins implicated in the one-carbon metabolism pathway (e.g., folate, cobalamin, and pyridoxal phosphate) are of particular interest in the elderly, because age-dependent conditions, including cardiovascular diseases and different kinds of cancer, may be partly explained by inadequate status of these vitamins [12]. Previous studies on tocopherol isoforms in elderly populations have mainly focused on potential associations with and effects on the immune system, infectious diseases, oxidative stress, and osteoporosis [13][14][15][16][17][18][19][20]. A study that investigated potential associations of circulating concentrations of both αand γ-tocopherol in elderly subjects in the general population of Germany was more focused on diet and lipids and did not include components related to one-carbon metabolism [21].…”
Section: Introductionmentioning
confidence: 99%